Significant Anti-CMV/BKV Effect of a Modern Everolimus-Based Regimen Comparted to Standard Tacrolimus-MPA Regimen in de Novo Kidney Transplant Recipients: Athena 12 months Data on Infections. (July 2018) - Dragun, Duska; Suwelack, Barbara; Sommerer, Claudia; Hauser, Ingeborg A; Witzke, Oliver; Hugo, Christian; Kamar, Nassim; Merville, Pierre; Schenker, Peter; Junge, Martina; Thaiss, Friedrich; Nashan, Björn
Abstract : Athena Study Group. Background: The ATHENA trial was designed to compare everolimus [EVR] in combination with tacrolimus [TAC] or cyclosporine A [CyA] vs. a standard regimen of mycophenolic acid [MPA] and TAC in de novo kidney transplant [Tx] recipients. Of specific interest was monitoring of infections with main focus on CMV and BKV. Methods: In this randomized 12 months [M] prospective, open-label study with 15 German and 12 French study sites, in total 612 patients [pts] were randomized 1:1:1 at time of Tx to either EVR (target trough: 3-8ng/ml M1-M12) +TAC (target trough: 4-8ng/ml M1-M3; 3-5ng/ml M3-M12), or EVR (3-8ng/ml M1-M12) + CyA (target trough: 75-125 ng/ml M1-M3; 50-100 ng/ml M3-M12) or to control TAC regimen (target trough: 4-8ng/ml M1-M3; 3-5ng/ml M3-M12) with MPA. All pts received ongoing steroids. Here we present M12 data on infections within ITT population with 208 EVR+TAC pts, 199 EVR+CyA pts and 205 TAC+MPA pts. Results: From randomization to M12 total incidence of infections was significantly higher in TAC+MPA group with 82% compared to 73% in EVR+TAC and 72% in EVR+CyA treated pts (p<0.05 for both EVR groups). In general, most frequent evet was urinary tract infection with similar incidences across groups: 41% vs 41% vs 40%, respectively. Major differences were seen for viral infections with an incidence of 41% in TAC+MPA vs 26% in EVR+TAC and 12% in EVR+CyA treatment groups (p<0.01). Of specific interest was incidence of BKV and CMV infections: BKV events were reported with 23% in TAC+MPA vs 17% in EVR+TAC vs 9% in EVR+CyA treatment groups (p<0.01) and CMV infections - as well significantly less under EVR treatment - with 21% in TAC+MPA vs 6% in EVR+TAC and 3% in EVR+CyA group (p<0.01). In addition to this more than three-fold difference for CMV infections between TAC+MPA and EVR-treatment, patients with CMV disease and/or recurrent CMV events occurred only in TAC+MPA group, not under EVR-treatment. Matching of CMV-donor/recipient status at baseline was balanced across groups for all risk-constellations and, of note: 3 months CMV-prophylaxis with valganciclovir for D+/R- and D+/R+ pts was requested per protocol. Conclusion: ATHENA as largest European KTx study confirmed comparable efficacy and safety of all 3 regimens together with beneficial outcomes on viral infections: significantly less viral infections for EVR-based treatment groups compared to TAC+MPA group and a significant, protective effect of EVR-based regimens vs CMV/BKV events was robustly demonstrated.